Demand for healthier and higher-priced processed foods in low-income communities: Experimental evidence from Mexico City - Dominguez-Viera, Marcos E.; Berg, Marrit van den; Donovan, Jason A.; Pérez Luna, Miriam E.; Ospina Rojas, Diana; Handgraaf, Michel (Elsevier, 2022)
Diets in Mexico, like many countries, have changed dramatically in recent decades, with increased consumption of processed foods being a major factor. Research suggests that unhealthy diets in low-income communities reflect limited access to healthy foods, combined with high costs and limited knowledge. Weak demand signals from these communities likely disincentivise the food industry from delivering healthier, often costlier, options. This paper explores the potential to market healthy processed foods to these areas. We elicited willingness to pay (WTP) for healthier but relatively more expensive processed foods in low-income communities of Mexico City. We implemented a BDM mechanism to elicit WTP, with half of the participants randomly receiving information regarding nutritional content and health benefits. Results suggested that WTP was considerable among low-income groups but higher among higher-income groups within these communities. While, in general, providing nutrition and health information did not influence WTP, it was effective for those with strong preferences for the processed food category used in the study. WTP was highest among females and younger consumers, those who had a small family and children below 12 years in the household.